KONFLIK KEKUASAAN DALAM ANGGARAN PEMILUKADA PROVINSI BALI - Gayatri, Gayatri (E-Jurnal Akuntansi, 2015)
The purpose of the research is to reveal the conflict of authority of budget Bali regional election. The data were collected through observations and dialogues with participants. Data analysis was conducted using Dahrendorf’s conflict theory. Dahrendorf’s conflict theory perceives regularities in society as a result of authority from super-ordinates to sub-ordinates. Authority is a rare resource. The conflicts of authority emerge to maintain the legitimacy of authority. The research finds that conflicts cannot be separated from the elections. Conflicts linger in the executive, legislative, and regional election authorities in Bali province. One of the main resources of authority is a budget. Organizations experiencing conflicts can make use of budget to maintain authority. The conflict of budget planning of regional elections ends with the excessive authority of budgeting team to cut the budget actors’ pay. The conflict of budget execution is shown by the authority of the incumbent and commissioners. The conflict of budget accountability ends with the authority of Financial Investigation Bureau of Indonesia to return the excess use of budget of regional elections. The implications of this study are the changes in the regulation of budgetary resources of regional elections from local (APBD) to state expenditure budget (APBN).
Keywords: Authority, budget, and conflicts.